High-temperature and high-humidity resistant high-speed medium-load self-lubricating fabric gasket and preparation method thereof

CN116554521BActive Publication Date: 2026-10-16LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310536072.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-12
Publication Date
2026-10-16
Estimated Expiration
2043-05-12

AI Technical Summary

Technical Problem

[0004]现有技术制备的织物增强型自润滑衬垫的主要不足在于:1)PTFE纤维减摩功能固定,工况适应性狭窄,特别在中载工况下,摩擦力矩相对较低,对自润滑织物的耐磨需求更大,而耐磨损寿命是使用者最关注的质量参数;2)自润滑织物结构中的PTFE纤维表面能较低,与树脂组分界面结合较低;3)自润滑衬垫对高温和高湿等苛刻工况环境适应性有限,缺乏针对热冲击和水分冲击特点而开发的环境适应性自润滑衬垫,对更为常见的高温、高湿和高线速度工况下自润滑衬垫使用寿命大大缩短的问题不能得到有效解决

Benefits of technology

[0021] This invention utilizes electrospinning to prepare a polyvinylidene fluoride (PVDF) electrospun layer as a protective layer placed on the surface of a fiber fabric, replacing the PTFE fiber lubricating layer fixed under the fabric structure in existing technologies. This significantly improves the mechanical strength, wear resistance, and load-bearing capacity of the self-lubricating pad structure, making it particularly suitable for high-speed friction and wear conditions under medium loads. Simultaneously, the large interfacial area and "capillary effect" of the micro-nano electrospun fibers enrich resin at the interface of the self-lubricating pad, forming a "network interpenetrating structure," which enhances the bonding between the electrospun protective layer, the resin layer, and the self-lubricating fabric layer on the surface of the self-lubricating pad. Furthermore, the strong hydrophobicity and temperature resistance of PVDF itself endow the self-lubricating pad with excellent environmental adaptability under harsh high-temperature and high-humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116554521B_ABST
    Figure CN116554521B_ABST
Patent Text Reader

Abstract

The application provides a high-speed medium-load self-lubricating fabric gasket resistant to high temperature and high humidity and a preparation method thereof, and relates to the technical field of self-lubricating composite materials. The polyvinylidene fluoride electrospinning layer prepared by electrospinning is used as a protective layer on the surface of the fiber fabric, which can improve the wear resistance and load capacity of the self-lubricating gasket, and is particularly suitable for high-speed friction and wear working conditions under medium load. Meanwhile, the micro-nano electrospinning fiber has a large interface area and a "capillary effect", which can enrich the resin on the interface of the self-lubricating gasket and form a "network interpenetrating structure", thereby enhancing the combination of the electrospinning layer and the resin layer and the self-lubricating fabric layer. In addition, the polyvinylidene fluoride has strong hydrophobicity and temperature resistance, and can endow the gasket with excellent environmental adaptability under harsh working conditions of high temperature and high humidity. The self-lubricating fabric gasket prepared by the application has excellent wear resistance and strong interfacial bonding force between the fabric and the resin, and is suitable for self-lubricating fabric gaskets resistant to high temperature and high humidity and applicable to high-speed medium load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of self-lubricating composite materials technology, and in particular to a high-temperature and high-humidity resistant, high-speed, mid-load self-lubricating fabric liner and its preparation method. Background Technology

[0002] Fabric-reinforced self-lubricating gaskets are the core component of self-lubricating spherical plain bearings. The combination of self-lubricating gaskets and metal bearings endows these bearings with features such as compact structure, maintenance-free operation, and impact resistance, meeting the needs of lubrication-free applications and solving the operational adaptability problems of traditional metal bearings, such as high-frequency vibration, contamination, corrosion, and short maintenance cycles. They have been widely used in aerospace, aviation, new energy, construction machinery, heavy trucks, and rail transportation.

[0003] The existing process for preparing fabric-reinforced self-lubricating pads typically involves the following steps: First, self-lubricating fabric weaving: Firstly, PTFE fibers are used as lubricating fibers to impart certain frictional properties to the self-lubricating fabric; secondly, various reinforcing fiber filaments or twisted reinforcing fibers are used as friction-reducing fibers to impart certain abrasion resistance to the self-lubricating fabric; finally, the self-lubricating fabric with the determined friction-reducing and abrasion-reducing functions is woven by fixing the fabric structure. Second, self-lubricating fabric impregnation: A resin component is used as an interface bonding material to fully bond with the self-lubricating fabric to obtain a prepreg. Third, the prepreg is cured and molded to obtain the self-lubricating pad.

[0004] The main shortcomings of existing fabric-reinforced self-lubricating gaskets are: 1) The friction-reducing function of PTFE fibers is fixed, resulting in narrow adaptability to various operating conditions. Especially under medium-load conditions, the friction torque is relatively low, which places greater demands on the wear resistance of the self-lubricating fabric. Wear life is the quality parameter that users are most concerned about; 2) The surface energy of PTFE fibers in the self-lubricating fabric structure is low, resulting in poor interfacial bonding with resin components; 3) The self-lubricating gaskets have limited adaptability to harsh operating conditions such as high temperature and high humidity. There is a lack of environmentally adaptable self-lubricating gaskets developed specifically for thermal shock and moisture shock characteristics. The problem of significantly shortened service life of self-lubricating gaskets under more common high temperature, high humidity, and high linear velocity conditions cannot be effectively solved. Summary of the Invention

[0005] In view of this, the purpose of this invention is to provide a high-temperature and high-humidity resistant, high-speed, medium-load self-lubricating fabric gasket and its preparation method. The self-lubricating fabric gasket prepared by this invention has excellent wear resistance and strong interfacial bonding between the fabric and resin, making it suitable for high-temperature and high-humidity harsh operating conditions and high-speed, medium-load applications.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing a high-temperature and high-humidity resistant, high-speed, mid-load self-lubricating fabric liner, comprising the following steps:

[0008] Using polyvinylidene fluoride solution as electrospinning solution, electrospinning is performed on the surface of fiber fabric to obtain a polyvinylidene fluoride electrospinned layer composite fabric.

[0009] The polyvinylidene fluoride electrospun layer composite fabric is impregnated in a resin impregnation solution and then dried to obtain a self-lubricating composite fabric prepreg.

[0010] The self-lubricating composite fabric prepreg is cured and molded to obtain the high-temperature and high-humidity high-speed medium-load self-lubricating fabric pad.

[0011] Preferably, the mass concentration of polyvinylidene fluoride in the electrospinning solution is 12-20%; and the molecular weight of the polyvinylidene fluoride is 300,000 to 1,000,000.

[0012] Preferably, the conditions for electrospinning include: a voltage of 12-15 kV, a spraying speed of the electrospinning solution of 1.0-2.0 mL / min, a receiving distance of 10-30 cm, and a spinning time of 10-180 min.

[0013] Preferably, the mass of the polyvinylidene fluoride electrospun layer in the polyvinylidene fluoride electrospun layer composite fabric is 1.67 × 10⁻⁶. -5 ~70×10 -5 g / cm 2 .

[0014] Preferably, the fiber fabric is woven from fibers using plain weave, twill weave, satin weave, or other weaving methods derived from the above; the fibers include reinforcing fibers and / or reinforcing fiber twisted fibers; the reinforcing fiber is a first fiber, and the reinforcing fiber twisted fiber is a twisted fiber of PTFE fiber and the first fiber, wherein the first fiber is one or more of para-aramid fiber, meta-aramid fiber, poly(p-phenylenebenzodioxazole) fiber, polyester fiber, polyimide fiber, glass fiber, and copper fiber.

[0015] Preferably, the fiber further includes PTFE fiber.

[0016] Preferably, the resin impregnation solution is a phenolic resin organic solution, and the mass concentration of the phenolic resin organic solution is 1-5%; the phenolic resin is a linear phenolic resin, a branched phenolic resin, or a phenolic-epoxy resin.

[0017] Preferably, the impregnation and drying are repeated until the polyvinylidene fluoride electrospun composite fabric gains 5-35% weight.

[0018] Preferably, the curing temperature is 140–190°C, the holding time is 0.5–2 h, and the heating rate from room temperature to the curing temperature is 1–8°C / min.

[0019] The present invention provides a high-temperature and high-humidity high-speed medium-load self-lubricating fabric liner prepared by the preparation method described above. The self-lubricating fabric liner includes fiber fabric, polyvinylidene fluoride electrospun fibers and resin components. The interfaces of the polyvinylidene fluoride electrospun fibers, resin components and fiber fabric form an interpenetrating network structure.

[0020] This invention provides a method for preparing a high-temperature, high-humidity, high-speed, mid-load self-lubricating fabric pad, comprising the following steps: using a polyvinylidene fluoride (PVDF) solution as an electrospinning solution, electrospinning is performed on the surface of a fiber fabric to obtain a PVDF electrospun layer composite fabric; the PVDF electrospun layer composite fabric is impregnated in a resin impregnation solution and dried to obtain a self-lubricating composite fabric prepreg; the self-lubricating composite fabric prepreg is cured and molded to obtain the high-temperature, high-humidity, high-speed, mid-load self-lubricating fabric pad. Compared with the prior art, this invention has the following beneficial effects:

[0021] This invention utilizes electrospinning to prepare a polyvinylidene fluoride (PVDF) electrospun layer as a protective layer placed on the surface of a fiber fabric, replacing the PTFE fiber lubricating layer fixed under the fabric structure in existing technologies. This significantly improves the mechanical strength, wear resistance, and load-bearing capacity of the self-lubricating pad structure, making it particularly suitable for high-speed friction and wear conditions under medium loads. Simultaneously, the large interfacial area and "capillary effect" of the micro-nano electrospun fibers enrich resin at the interface of the self-lubricating pad, forming a "network interpenetrating structure," which enhances the bonding between the electrospun protective layer, the resin layer, and the self-lubricating fabric layer on the surface of the self-lubricating pad. Furthermore, the strong hydrophobicity and temperature resistance of PVDF itself endow the self-lubricating pad with excellent environmental adaptability under harsh high-temperature and high-humidity conditions.

[0022] Furthermore, the present invention uses reinforcing fibers and / or reinforcing fiber twisted fibers to weave fiber fabrics, and the PVDF electrospinning layer ensures that the self-lubricating pad has a low frictional torque, while also improving the wear resistance, wear life, interfacial bonding strength with resin, and load-bearing capacity of the self-lubricating pad.

[0023] The self-lubricating fabric pad prepared by this invention has excellent wear resistance and strong bonding force between the fabric and resin interface. It is a self-lubricating fabric pad that can withstand harsh working conditions such as high temperature (100-200℃) and high humidity (50%RH-95%RH) and is suitable for high speed and medium load (30-200MPa load, linear speed 4-20m / min).

[0024] The results of the examples show that the "interpenetrating network" structure formed by the electrospun fibers, fabric interface and resin components on the surface of the self-lubricating fabric liner prepared by the present invention has good bonding and high peel strength. Moreover, after tribological tests with a load of 37.5 MPa and a linear speed of 15.7 m / min, whether in high temperature environment simulation test (110℃) or high humidity environment simulation test (95% RH), the average wear rate and average friction coefficient before and after the test are better than the original sample without the electrospun lubricating layer. Attached Figure Description

[0025] Figure 1 This is a field emission scanning electron microscope (FESEM) image of the uncured surface of composite material 1;

[0026] Figure 2 This is a field emission scanning electron microscope (FESEM) image of the uncured surface of composite material 2;

[0027] Figure 3 This is a field emission scanning electron microscope (FESEM) image of the uncured cross section of composite material 2;

[0028] Figure 4 This is a field emission scanning electron microscope (FESEM) image of the uncured cross section of composite material 2;

[0029] Figure 5 This is a field emission scanning electron microscope (FESEM) image of the cured cross section of composite material 2;

[0030] Figure 6 These are the DSC spectra of uncured composite material 1 and composite material 4;

[0031] Figure 7 These are the ATR infrared spectra of uncured composite materials 1-4;

[0032] Figure 8 This is a bar chart showing the average wear rate of composite materials before and after exposure to high-temperature environments (sections 1-4).

[0033] Figure 9 This is a bar chart showing the average friction coefficients of the composite materials before and after exposure to high-temperature environments (sections 1-4).

[0034] Figure 10 This is a SEM image of composite material 1 after undergoing a high-temperature simulated environment test;

[0035] Figure 11 This is a SEM image of composite material 2 after undergoing a high-temperature simulated environment test;

[0036] Figure 12 This is a SEM image of the wear marks on composite material 1 after undergoing a high-temperature simulated environment test;

[0037] Figure 13This is a SEM image of the wear marks on the composite material 2 after undergoing a high-temperature simulated environment test;

[0038] Figure 14 This is a bar chart showing the average wear rate of the composite material before and after exposure to high humidity environments (sections 1-4).

[0039] Figure 15 This is a bar chart showing the average friction coefficient of the composite material before and after exposure to high humidity environments (sections 1-4).

[0040] Figure 16 This is a SEM image of composite material 1 after undergoing a high humidity simulated environment test;

[0041] Figure 17 This is a SEM image of composite material 2 after undergoing a high humidity simulated environment test;

[0042] Figure 18 This is a SEM image of the wear marks on composite material 1 after undergoing a high humidity simulated environment test;

[0043] Figure 19 This is a SEM image of the wear marks on composite material 2 after undergoing a high humidity simulated environment test. Detailed Implementation

[0044] This invention provides a method for preparing a high-temperature and high-humidity resistant, high-speed, mid-load self-lubricating fabric liner, comprising the following steps:

[0045] Using polyvinylidene fluoride solution as electrospinning solution, electrospinning is performed on the surface of fiber fabric to obtain a polyvinylidene fluoride electrospinned layer composite fabric.

[0046] The polyvinylidene fluoride electrospun layer composite fabric is impregnated in a resin impregnation solution and then dried to obtain a self-lubricating composite fabric prepreg.

[0047] The self-lubricating composite fabric prepreg is cured and molded to obtain the high-temperature and high-humidity high-speed medium-load self-lubricating fabric pad.

[0048] Unless otherwise specified, all raw materials involved in this invention are commercially available products well known to those skilled in the art.

[0049] This invention uses a polyvinylidene fluoride (PVDF) solution as the electrospinning solution to perform electrospinning on the surface of a fiber fabric, thereby obtaining a PVDF electrospun layer composite fabric. In this invention, the PVDF solution is preferably prepared by dissolving PVDF in a mixed solvent of N,N-dimethylformamide and acetone, wherein the volume ratio of N,N-dimethylformamide to acetone in the mixed solvent is preferably 4:1. In this invention, the mass concentration of PVDF in the electrospinning solution is preferably 12-20%, more preferably 13-15%; the molecular weight of the PVDF is preferably 300,000 to 1,000,000, specifically 370,000, 625,000, or 1,000,000. Compared to polytetrafluoroethylene (PTFE) with its poor processing performance, polychlorotrifluoroethylene (PCTFE) with its difficult molding process, perfluoroethylene propylene (PEP or 46) with its poor mechanical properties, polyvinylidene fluoride (PVF) with its poor heat and corrosion resistance, and fusible polytetrafluoroethylene (PFA) with its high price, the polyvinylidene fluoride (PVDF) selected in this invention has unique advantages such as high mechanical strength, heat resistance, corrosion resistance, weather resistance, oxidation resistance, radiation resistance, non-aging, good processing performance, and long service life. Furthermore, this invention controls the molecular weight of polyvinylidene fluoride to 300,000 to 1,000,000, which is conducive to forming an electrospun fiber protective layer with suitable mechanical properties. This ensures the rapid formation of a protective film at the friction pair interface while also taking into account a certain degree of wear resistance.

[0050] In this invention, the fiber fabric is preferably woven from fibers using plain weave, twill weave, satin weave, or other weaving methods derived from the above. In this invention, the fibers preferably include reinforcing fibers and / or reinforcing fiber twisted fibers; the reinforcing fiber is preferably a first fiber, and the reinforcing fiber twisted fiber is preferably a twisted fiber of PTFE fiber and the first fiber. The first fiber is preferably one or more of para-aramid fiber, meta-aramid fiber, poly(p-phenylenebenzodioxazole) (PBO) fiber, polyester fiber, polyimide fiber, glass fiber, and copper fiber; the fibers also preferably include PTFE fiber, meaning the fiber fabric is woven from one or two of the reinforcing fibers and reinforcing fiber twisted fibers with PTFE fiber. In an embodiment of this invention, the fiber fabric is preferably woven from para-aramid fiber filaments using a twill weave. Reinforcing fibers, represented by para-aramid fiber, have higher abrasion resistance and surface energy than PTFE fiber, which can greatly improve the fabric's abrasion life, the bonding strength with the resin interface, and the load-bearing capacity of the self-lubricating pad.

[0051] In this invention, the preferred conditions for electrospinning include: a voltage preferably of 12–15 kV, more preferably 13–14 kV; a spraying speed of the electrospinning solution preferably of 1.0–2.0 mL / min, more preferably 1.0–1.5 mL / min; a receiving distance preferably of 10–30 cm, more preferably 10–20 cm; and a spinning time preferably of 10–180 min, more preferably 30–180 min. In this invention, the mass of the polyvinylidene fluoride electrospinned layer in the polyvinylidene fluoride electrospinned layer composite fabric is 1.67 × 10⁻⁶. -5 ~70×10 -5 g / cm 2 More preferably 5×10 -5 ~70×10 -5 g / cm 2 Electrospinning is a polymer material processing technology in which a polymer solution is stretched in a strong electric field to form a jet, and the solvent evaporates and solidifies in the jet to form micro- and nanofibers. It has the advantages of simple process, wide range of materials, large-scale preparation and adjustable content. This invention uses electrospinning to prepare a polyvinylidene fluoride (PVDF) protective layer on the surface of the underlying fiber fabric. Functionally, it can significantly improve the mechanical strength, wear resistance and load-bearing capacity of the self-lubricating pad structure, and is particularly suitable for friction and wear conditions under high speed and medium load. In terms of process, the formed micro- and nano-electrospun fibers penetrate the fabric vertically and have a large interface area and "capillary effect", which is conducive to resin enrichment and the formation of "interpenetrating network structure". This enhances the bonding between the electrospinning protective layer on the surface of the self-lubricating pad, the resin layer and the self-lubricating fabric layer. At the same time, due to the strong hydrophobicity and temperature resistance of PVDF itself, it can also give the self-lubricating pad excellent environmental adaptability in harsh conditions such as high temperature and high humidity.

[0052] After obtaining the polyvinylidene fluoride (PVDF) electrospun composite fabric, the present invention impregnates the PVDF electrospun composite fabric in a resin impregnation solution and then dries it to obtain a self-lubricating composite fabric prepreg. In the present invention, the resin impregnation solution is preferably a phenolic resin organic solution, the mass concentration of which is preferably 1-5%, more preferably 3%; the phenolic resin is preferably linear phenolic resin, branched phenolic resin, or phenolic-epoxy resin, appearing as a brownish-red liquid, with free phenol ≤2.5wt%, a viscosity of 150-200 (S / 25℃), and a solid content ≥75wt%; the organic solvent used in the phenolic resin organic solution is preferably one or more of ethanol, methanol, acetone, ethyl acetate, and tetrahydrofuran. In the present invention, the impregnation and drying are preferably repeated until the PVDF electrospun composite fabric gains 5-35% in weight, wherein the time for each impregnation is preferably 15-30 minutes. Through resin impregnation, a self-lubricating fabric prepreg with an interpenetrating network surface is formed.

[0053] After obtaining the self-lubricating composite fabric prepreg, the present invention cures the self-lubricating composite fabric prepreg to obtain the high-temperature and high-humidity high-speed mid-load self-lubricating fabric liner. Preferably, the present invention uses phenolic resin to bond the self-lubricating composite fabric prepreg to the surface of a metal substrate, applies a pressure of 0.03–0.3 MPa, and then cures it. The present invention does not have special requirements for the metal substrate; any metal substrate well-known to those skilled in the art can be used, such as 17-4PH or Cr9Mo steel. The preferred dimensions of the metal substrate are Φ45 mm and the preferred thickness is 8 mm. In the present invention, the curing temperature is preferably 140–190°C, more preferably 150–180°C, the holding time is preferably 0.5–2 h, and the heating rate from room temperature to the curing temperature is preferably 1–8°C / min.

[0054] This invention provides a high-temperature, high-humidity, high-speed, medium-load self-lubricating fabric liner prepared by the preparation method described above. The self-lubricating fabric liner comprises a fiber fabric, polyvinylidene fluoride (PVDF) electrospun fibers, and a resin component. The PVDF electrospun fibers, resin component, and fiber fabric form an interpenetrating network structure at their interfaces. The self-lubricating fabric liner provided by this invention exhibits excellent wear resistance and strong interfacial bonding between the fabric and resin. It is a self-lubricating fabric liner suitable for high-temperature and high-humidity harsh operating conditions and applicable to high-speed, medium-load applications, demonstrating excellent wear resistance under both high-temperature and high-humidity conditions.

[0055] To further illustrate the present invention, the high-temperature and high-humidity resistant high-speed mid-load self-lubricating fabric liner and its preparation method provided by the present invention are described in detail below with reference to examples, but these should not be construed as limiting the scope of protection of the present invention.

[0056] Comparative Example 1

[0057] The preparation steps for self-lubricating fabric liners are as follows:

[0058] (1) Using para-aramid fiber filament as the weaving fiber, a bottom fiber fabric with enhanced abrasion resistance is prepared with a twill fabric structure.

[0059] (2) The fiber fabric in (1) is immersed in the resin impregnation solution for 30 minutes, taken out and dried. The impregnation process is repeated until the fabric weight increases by 30% to obtain a self-lubricating composite fabric prepreg; wherein the resin impregnation solution is prepared by dispersing 30g of phenolic resin in 900mL of acetone.

[0060] (3) The self-lubricating composite fabric prepreg in (2) is bonded to the surface of a stainless steel substrate (17-4PH, martensitic precipitation hardening stainless steel) with phenolic resin, and a pressure of 0.03 MPa is applied. The temperature is raised to 180°C at a rate of 8°C / min at room temperature and cured at this temperature for 2 hours to obtain a self-lubricating fabric pad (without electrostatic spinning lubrication layer), which is referred to as self-lubricating fabric pad composite material 1.

[0061] Example 1

[0062] The preparation steps for self-lubricating fabric liners are as follows:

[0063] (1) Using para-aramid fiber filament as the weaving fiber, a bottom fiber fabric with enhanced abrasion resistance is prepared with a twill fabric structure.

[0064] (2) A 13% (w / w) electrospinning solution was prepared using polyvinylidene fluoride (PVDF) resin with a molecular weight of 370,000. Under the action of a 13kV electric field, the electrospinning solution was sprayed onto the underlying fiber fabric at a spraying speed of 1.0 mL / min (receiving distance of 15 cm) to obtain a PVDF electrospinned layer composite fabric (the mass of the PVDF electrospinned layer is 66.7 × 10⁻⁶). -5 g / cm 2 );

[0065] (3) The PVDF electrospun composite fabric is immersed in the resin impregnation solution for 30 minutes, then removed and dried. The immersion and drying process is repeated until the fabric weight increases by 30% to obtain the self-lubricating composite fabric prepreg. The resin impregnation solution is prepared by dispersing 30g of phenolic resin in 900mL of acetone.

[0066] (4) The self-lubricating composite fabric prepreg in (3) is bonded to the surface of a stainless steel substrate (17-4PH, martensitic precipitation hardening stainless steel) with phenolic resin, and a pressure of 0.03 MPa is applied. The temperature is raised to 180°C at a rate of 8°C / min at room temperature and cured at this temperature for 2 hours to obtain a self-lubricating fabric pad, which is referred to as self-lubricating fabric pad composite material 2.

[0067] Example 2

[0068] The molecular weight of the PVDF resin in step (2) of Example 1 was replaced with 625,000, and the rest was the same as in Example 1, to obtain a self-lubricating fabric pad, which is denoted as self-lubricating fabric pad composite material 3.

[0069] Example 3

[0070] The molecular weight of the PVDF resin in step (2) of Example 1 was replaced with 1 million, and the rest was the same as in Example 1, to obtain a self-lubricating fabric liner, which is denoted as self-lubricating fabric liner composite material 4.

[0071] The morphology and performance of the self-lubricating fabric liner composite materials 1-4 (abbreviated as composite materials 1-4) prepared in Comparative Example 1 and Examples 1-3 were tested as follows:

[0072] 1. Morphology Analysis of Self-Lubricating Fabric Pad Composite Materials

[0073] Figure 1 This is a field emission scanning electron microscope (FESEM) image of the uncured surface of composite material 1. Due to the limited compatibility between the resin and the fabric, Figure 1 Obvious voids can be found in the structure, and these voids are precisely the shortcomings that affect the structure and performance of the self-lubricating gasket.

[0074] Figure 2 This is a field emission scanning electron microscope (FESEM) image of the uncured surface of composite material 2, showing good bonding between the electrospun nanofibers and the underlying fabric in the vertical direction. No void structure was observed on the uncured surface of the self-lubricating fabric pad 2, and the electrospun fibers perpendicular to the fabric surface showed good bonding with the resin interface.

[0075] Figure 3 and Figure 4 These are field emission scanning electron microscope (FESEM) images of the uncured cross-section of composite material 2 at different scales. Figure 3 and Figure 4 The "interpenetrating network" structure formed by the electrospun fibers perpendicular to the fabric surface and the underlying fabric is visible, as well as the resin components enriched on the periphery of the electrospun fibers and the surface of the uncured self-lubricating pad under the action of "capillaries".

[0076] Figure 5 This is a field emission scanning electron microscope (FESEM) image of the cured cross-section of composite material 2. It shows the "interpenetrating network" structure formed by the electrospun fibers, fabric interface, and resin components on the surface of the cured self-lubricating pad. This structure is the structural basis for the high-speed, mid-load self-lubricating pad prepared in this invention, which is resistant to harsh conditions such as high temperature and high humidity.

[0077] 2. Differential scanning calorimetry (DSC) analysis of self-lubricating fabric pads

[0078] Figure 6 The figures show the DSC spectra of uncured composite material 1 and composite material 4. As can be seen from the figures, due to the barrier effect of the electrospinning layer, the thermal effect of the self-lubricating pad composite material 4 during the curing process is significantly lower than that of composite material 1, which indirectly verifies the "thermal insulation" effect of the electrospinning layer.

[0079] 3. Attenuated Total Reflectance (ATR) Infrared Spectral Analysis of Self-Lubricating Fabric Pads

[0080] Figure 7 This is the ATR infrared spectrum of the uncured composite material. The ATR spectrum of composite material 2 at 3300 cm⁻¹ is visible. -1 The absorption peak intensity at point 2 is significantly stronger than that of other composite materials, indicating that composite material 2 has the strongest "capillary effect" on the resin component.

[0081] 4. Peel strength analysis of self-lubricating fabric pads

[0082] 4.1 Preparation of test samples for force peel test of self-lubricating gasket composite material

[0083] Composite material peel strength test sample:

[0084] The self-lubricating composite fabric prepregs of Comparative Example 1 and Examples 1-3 were bonded to the surface of 2024 aluminum alloy with phenolic resin, and a pressure of 0.03 MPa was applied. The temperature was increased to 180°C at a rate of 8°C / min at room temperature and cured at this temperature for 2 hours to obtain the peel strength test samples of self-lubricating pad composite materials 1-4.

[0085] 4.2. The self-lubricating gasket composite materials 1-4 prepared in 4.1 were subjected to high temperature and high humidity environment simulation tests.

[0086] 4.2.1 High-Temperature Environment Simulation Test

[0087] The self-lubricating fabric pad was subjected to a high-temperature environment simulation test by placing it at 100°C for 24 hours.

[0088] 4.2.2 High Humidity Environment Simulation Test

[0089] The self-lubricating fabric liner was subjected to a high humidity environment simulation test by repeating the following seven cycles: ① heat to 60℃ (normal indoor humidity) and maintain for 18 minutes; ② maintain 60℃ + 95% RH for 2 hours; ③ maintain 60℃ + 95% RH for 16 hours; ④ maintain 30℃ + 95% RH for 8 hours.

[0090] 4.3 Environmental tests were conducted according to the environmental simulation test procedures outlined in 4.2.1 and 4.2.2 above. Then, the peel strength test of the composite material was performed according to GB / T2790-1995. The peel strength data of test samples 1–4 of the self-lubricating gasket composite material are shown in Tables 1 and 2:

[0091] Table 1 Peel strength of composite materials after high-temperature environmental simulation test

[0092]

[0093] As shown in Table 1, after undergoing high-temperature environment simulation tests, the peel strength of composite material 1 in the warp and weft directions was 0.69 N / mm and 0.61 N / mm, respectively; the peel strength of composite material 2 in the warp and weft directions was 1.57 N / mm and 1.30 N / mm, respectively; the peel strength of composite material 3 in the warp and weft directions was 0.92 N / mm and 1.07 N / mm, respectively; and the peel strength of composite material 4 in the warp and weft directions was 1.73 N / mm and 1.03 N / mm, respectively.

[0094] Table 2 Peel strength of composite materials after high humidity environment simulation test

[0095]

[0096] As shown in Table 2, after undergoing a high humidity environment simulation test, the peel strength of composite material 1 in the warp and weft directions was 0.72 N / mm and 1.15 N / mm, respectively; the peel strength of composite material 2 in the warp and weft directions was 0.88 N / mm and 1.16 N / mm, respectively; the peel strength of composite material 3 in the warp and weft directions was 1.50 N / mm and 1.94 N / mm, respectively; and the peel strength of composite material 4 in the warp and weft directions was 1.03 N / mm and 1.22 N / mm, respectively.

[0097] As can be seen from Tables 1 and 2, the effect of high temperature environment on resin peel strength is greater than that of high humidity environment, and the electrospinning protective layer has a significant shielding effect against high heat and moisture impact.

[0098] 5. High-temperature and high-humidity tribological performance test

[0099] 5.1 High-Temperature Friction and Wear Performance Test

[0100] Test Method: On the Xuanwu No. 3 friction and wear testing machine, under determined load, linear velocity, and test time, a 2mm diameter stainless steel bolt made of 45 steel was used as the friction pair to conduct friction and wear tests on the self-lubricating gasket composite material. The average friction coefficient and real-time friction coefficient data were measured by the equipment. The wear depth data was obtained by measuring the wear track depth using a dial indicator with an accuracy of 0.001mm. The surface temperature of the worn surface was measured by a temperature sensor in direct contact with the friction pair bolt. Wear Rate Calculation Method: ω=V / (PL), where V represents the wear volume (m³). 3 P represents the load (N), and L is the sliding distance (m).

[0101] The self-lubricating gasket composite materials 1-4 prepared above were subjected to friction and wear testing for 120 minutes on a Xuanwu No. 3 friction and wear testing machine under the conditions of a load of 37.5 MPa, a linear velocity of 15.7 m / min, and an ambient temperature of 110℃ (provided by a heating furnace to simulate a high-temperature environment, while simultaneously conducting high-temperature wear tests). Each test was repeated three times, and then the average of the three average friction coefficients and average wear rates was calculated again. The test results are shown in Table 3. Figure 8 and Figure 9 As shown.

[0102] Table 3 Tribological properties of composite materials after high-temperature environmental simulation tests

[0103]

[0104] As shown in Table 3, Figure 8 and Figure 9 As shown, the average wear rate of composite material 1 increased from the original value of 0.3723*10 -14 m 3 / Nm, increased to 0.5665*10 -14 m 3 / Nm; The original average wear rate of composite material 2 is 0.1363*10 -14 m 3 / Nm, still 0.1398*10 after the experiment. -14 m 3 / Nm; The average wear rate of composite material 3 increased from the original value of 0.1094*10 -14 m 3 / Nm, rising to 0.1374*10 -14 m 3 / Nm; The average wear rate of composite material 4 increased from the original value of 0.1318*10 -14 m 3 / Nm, decreased to 0.1104*10 -14 m 3 / Nm. The average friction coefficient of composite material 1 changed from the original value of 0.2653 to 0.2545 after the test; the average friction coefficient of composite material 2 changed from the original value of 0.1236 to 0.1365 after the test; the average friction coefficient of composite material 3 changed from the original value of 0.1159 and remained at 0.1206 after the environmental simulation test; the average friction coefficient of composite material 4 changed from the original value of 0.1204 to 0.1434 after the test.

[0105] It is evident that the electrospun protective layer provides excellent thermal shock protection, with both the average wear rate and average friction coefficient being superior to the original sample without the electrospun lubricating layer before and after environmental simulation tests. Specifically, without environmental simulation tests, composite material 4 showed a 64.60% reduction in average wear rate and a 54.62% reduction in average friction coefficient compared to unmodified composite material 1. After high-temperature environmental simulation tests, composite material 4 showed an 80.51% reduction in average wear rate and a 44.65% reduction in average friction coefficient compared to unmodified composite material 1.

[0106] Analysis of wear track morphology of self-lubricating gasket after high-temperature simulated environment test:

[0107] Figure 10 and Figure 11 These are SEM images of composite material 1 and composite material 2 after being placed at 110℃ for 120 minutes. As can be seen from the images, due to the effects of the high-temperature simulated environment test, composite material 1 exhibits "delamination" and "crack" morphology on its surface; while composite material 2, due to the protection of the electrospinning layer, only exposes a few fine pores on its surface.

[0108] Figure 12 and Figure 13 The images show SEM images of the worn surfaces of composite materials 1 and 2 after a tribological test at 37.5 MPa, 15.7 m / min, 110 °C, and 120 min. The images show that composite material 1 suffers severe surface damage, with the resin layer completely peeling off; while composite material 2 shows only partial surface damage, demonstrating the significant protective effect of the electrospun layer.

[0109] 5.2 High Wet Friction and Wear Performance Test

[0110] The self-lubricating fabric pad composites 1-4 underwent environmental simulation testing as described in section 4.2.2 above, followed by tribological and wear performance testing (room temperature test) according to the test method described in section 5.1 above. The test results are shown in Table 4. Figure 14 and Figure 15 As shown.

[0111] Table 4. Tribological properties of composite materials after high humidity environment simulation test

[0112]

[0113] As shown in Table 4, Figure 14 and Figure 15 As shown, the self-lubricating gasket composite materials 1-4 prepared above were subjected to friction and wear testing for 120 minutes on a Xuanwu No. 3 friction and wear testing machine under a load of 37.5 MPa and a linear velocity of 15.7 m / min. The average wear rate of composite material 1 increased from the original value of 0.3723*10-14 m 3 / Nm, decreased to 0.3104*10 after environmental testing. -14 m 3 / Nm; The average wear rate of composite material 2 increased from the original value of 0.1363*10 -14 m 3 / Nm, increased to 0.1856*10 after environmental testing. -14 m 3 / Nm; The original average wear rate of composite material 3 is 0.1094*10 -14 m 3 / Nm, increased to 0.2065*10 after environmental testing. -14 m 3 / Nm; The average wear rate of composite material 4 increased from the original value of 0.1318*10 -14 m 3 / Nm, decreased to 0.1158*10 -14 m 3 / Nm. The average friction coefficient of composite material 1 changed from the original value of 0.2653 to 0.2088 after the environmental simulation test; the average friction coefficient of composite material 2 changed from the original value of 0.1236 to 0.1376 after the environmental simulation test; the average friction coefficient of composite material 3 decreased from the original value of 0.1159 to 0.0987 after the environmental simulation test; the average friction coefficient of composite material 4 remained at 0.1243 after the environmental simulation test, with an original value of 0.1204.

[0114] It is evident that the electrospun protective layer provides excellent protection against high humidity environments, with both the average wear rate and average friction coefficient being superior to the original sample without the electrospun lubricating layer before and after environmental simulation tests. In particular, composite material 4 exhibits both excellent wear resistance and lubrication properties. Without environmental simulation tests, the average wear rate of composite material 4 was reduced by 64.60% compared to the unmodified composite material 1, and the average friction coefficient was reduced by 54.62%. After environmental simulation tests, the average wear rate of composite material 4 was reduced by 62.69% compared to the unmodified composite material 1, and the average friction coefficient was reduced by 40.47%.

[0115] Analysis of wear track morphology of self-lubricating gasket after high humidity simulated environment test:

[0116] Figure 16 and Figure 17 These are SEM images of composite material 1 and composite material 2 after undergoing a high humidity simulated environment test. As can be seen from the images, due to the effects of the high humidity simulated environment test, a large number of "crack" morphologies appeared on the surface of composite material 1; while the surface of composite material 2, due to the protection of the electrospinning layer, only exposed a few electrospinned fibers encapsulating the resin.

[0117] Figure 18 and Figure 19 These are SEM images of the worn surfaces of composite materials 1 and 2 after undergoing high humidity simulated environment testing, followed by friction and wear tests at 37.5 MPa, 15.7 m / min, and 120 min. The images show that composite material 1 exhibits resin detachment and cracks on its surface, with some of the underlying fabric structure damaged; while composite material 2 shows only partial surface damage and detachment, indicating that the electrospun layer resists water penetration and maintains good wear performance.

[0118] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a high-temperature, high-humidity, high-speed, mid-load self-lubricating fabric liner, characterized in that, Includes the following steps: Using polyvinylidene fluoride solution as electrospinning solution, electrospinning is performed on the surface of fiber fabric to obtain a polyvinylidene fluoride electrospinned layer composite fabric. The mass of the polyvinylidene fluoride electrospun layer in the polyvinylidene fluoride electrospun layer composite fabric is 1.67 × 10⁻⁶. -5 ~70×10 -5 g / cm 2 ; The polyvinylidene fluoride electrospun layer composite fabric is impregnated in a resin impregnation solution and then dried to obtain a self-lubricating composite fabric prepreg; the resin impregnation solution is a phenolic resin organic solution. The self-lubricating composite fabric prepreg is cured and molded to obtain the high-temperature and high-humidity high-speed medium-load self-lubricating fabric pad.

2. The preparation method according to claim 1, characterized in that, The mass concentration of polyvinylidene fluoride in the electrospinning solution is 12-20%; the molecular weight of the polyvinylidene fluoride is 300,000 to 1,000,000.

3. The preparation method according to claim 1 or 2, characterized in that, The conditions for electrospinning include: a voltage of 12-15 kV, an electrospinning solution spraying speed of 1.0-2.0 mL / min, a receiving distance of 10-30 cm, and a spinning time of 10-180 min.

4. The preparation method according to claim 1, characterized in that, The fiber fabric is woven from fibers using plain weave, twill weave, satin weave, or other weaving methods derived from the above; the fibers include reinforcing fibers and / or reinforcing fiber twisted fibers; the reinforcing fiber is a first fiber, and the reinforcing fiber twisted fiber is a twisted fiber of PTFE fiber and the first fiber, wherein the first fiber is one or more of para-aramid fiber, meta-aramid fiber, poly(p-phenylenebenzodioxazole) fiber, polyester fiber, polyimide fiber, glass fiber, and copper fiber.

5. The preparation method according to claim 4, characterized in that, The fibers also include PTFE fibers.

6. The preparation method according to claim 1, characterized in that, The mass concentration of the phenolic resin organic solution is 1-5%; the phenolic resin is a linear phenolic resin, a branched phenolic resin, or a phenolic-epoxy resin.

7. The preparation method according to claim 1, characterized in that, The impregnation and drying processes are repeated until the polyvinylidene fluoride electrospun composite fabric gains 5-35% in weight.

8. The preparation method according to claim 1, characterized in that, The curing temperature is 140~190℃, the holding time is 0.5~2h, and the heating rate from room temperature to the curing temperature is 1~8℃ / min.

9. A high-temperature and high-humidity high-speed mid-load self-lubricating fabric liner prepared by the preparation method according to any one of claims 1 to 8, wherein the self-lubricating fabric liner comprises a fiber fabric, polyvinylidene fluoride electrospun fibers and a resin component, wherein the interfaces of the polyvinylidene fluoride electrospun fibers, the resin component and the fiber fabric form an interpenetrating network structure.

Citation Information

Patent Citations

  • Polyvinylidene fluoride piezoelectric non-woven fabric, and preparing method and application thereof

    CN103469485A

  • Electrospun nanofiber film-fabric composite coating material and preparation method

    CN110253984A